Biological impact of restrictive and liberal fluid strategies at low and high PEEP levels on lung and distal organs in experimental acute respiratory distress syndrome - Felix, Nathane S.; Maia, Ligia A.; Rocha, Nazareth N.; Rodrigues, Gisele C.; Medeiros, Mayck; da Silva, Leticia A.; Baldavira, Camila M.; Fernezlian, Sandra de M.; Eher, Esmeralda M.; Capelozzi, Vera L.; Malbrain, Manu L. N. G.; Pelosi, Paolo; et al. (Frontiers in Physiology, 2022)
Background: Fluid regimens in acute respiratory distress syndrome (ARDS) are conflicting. The amount of fluid and positive end-expiratory pressure (PEEP) level may interact leading to ventilator-induced lung injury (VILI). We therefore evaluated restrictive and liberal fluid strategies associated with low and high PEEP levels with regard to lung and kidney damage, as well as cardiorespiratory function in endotoxin-induced ARDS. Methods: Thirty male Wistar rats received an intratracheal instillation of Escherichia coli lipopolysaccharide. After 24 h, the animals were anesthetized, protectively ventilated (VT=6 mL/kg), and randomized to restrictive (5 mL/kg/h) or liberal (40 mL/kg/h) fluid strategies (Ringer lactate). Both groups were then ventilated with PEEP=3 cmH2O (PEEP3) and PEEP=9 cmH2O (PEEP9) for 1 h (n=6/group). Echocardiography, arterial blood gases, and lung mechanics were evaluated throughout the experiments. Histologic analyses were done on the lungs, and molecular biology was assessed in lungs and kidneys using six non-ventilated animals with no fluid therapy. Results: In lungs, the liberal group showed increased transpulmonary plateau pressure compared with the restrictive group (liberal, 23.5 ± 2.9 cmH2O; restrictive, 18.8 ± 2.3 cmH2O, p=0.046) under PEEP=9 cmH2O. Gene expression associated with inflammation (interleukin [IL]-6) was higher in the liberal-PEEP9 group than the liberal-PEEP3 group (p=0.006) and restrictive-PEEP9 (p=0.012), Regardless of the fluid strategy, lung mechanical power and the heterogeneity index were higher, whereas birefringence for claudin-4 and zonula-ocludens-1 gene expression were lower in the PEEP9 groups. Perivascular edema was higher in liberal groups, regardless of PEEP levels. Markers related to damage to epithelial cells (club cell secreted protein [CC16]) and the extracellular matrix (syndecan) were higher in the liberal-PEEP9 group than the liberal-PEEP3 group (p=0.010 and p=0.024, respectively). In kidneys, the expression of IL-6 and neutrophil gelatinase-associated lipocalin was higher in PEEP9 groups, regardless of the fluid strategy. For the liberal strategy, PEEP=9 cmH2O compared with PEEP=3 cmH2O reduced the right ventricle systolic volume (37%) and inferior vena cava collapsibility index (45%). Conclusions: The combination of a liberal fluid strategy and high PEEP led to more lung damage. The application of high PEEP, regardless of the fluid strategy, may also be deleterious to kidneys.